2022
DOI: 10.1002/ejic.202101107
|View full text |Cite
|
Sign up to set email alerts
|

M(II) (M=Cu, Ni) Assisted C−S Bond Cleavage and Oxidative Dehydrogenation of Amine on Non‐Innocent Salen Type Ligand Platforms by Varying Nitrogen vs. Sulfur Coordination Atoms

Abstract: Herein, we report two newly synthesized salen‐type ligands, 2,3‐bis((3,5‐di‐tert‐butyl‐2‐hydroxybenzyl)thio)maleonitrile (H2L1) and 2,3‐bis((3,5‐di‐tert‐butyl‐2‐hydroxybenzyl)amino)malenonitrile (H4L2), bearing different coordination sites (sulfur vs amine) at maleonitrile tethered moiety to investigate metal mediated non‐innocence chemistry of these ligands. Upon metallation, ligand H2L1 did not yield simple metal‐ligand complex, rather ligand was split into two organic fragments, dithiolene moiety (mnt)2− an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…The empirical factor (g ∥ /A ∥ ) was 127 cm −1 suggesting that square planar structures fall in the range of 105–135 cm −1 . According to the Peisach–Blumberg diagram, [41] these parameter values predicted a complex of Cu II coordinated by mixed donor N and O atoms in distorted tetragonal or square‐pyramidal geometry [42–45] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical factor (g ∥ /A ∥ ) was 127 cm −1 suggesting that square planar structures fall in the range of 105–135 cm −1 . According to the Peisach–Blumberg diagram, [41] these parameter values predicted a complex of Cu II coordinated by mixed donor N and O atoms in distorted tetragonal or square‐pyramidal geometry [42–45] …”
Section: Resultsmentioning
confidence: 99%
“…According to the Peisach-Blumberg diagram, [41] these parameter values predicted a complex of Cu II coordinated by mixed donor N and O atoms in distorted tetragonal or squarepyramidal geometry. [42][43][44][45] The EPR spectrum of YGM1 also showed a rhombic signal with g 1,2,3 = 2.222, 2.087, 2.081 and A k =190×10 À 4 cm À 1 (g k /A k = 117 cm À 1 ) which were slightly different from the EPR parameters values of YGM2 suggesting different ligand environment and/or geometry at Cu II -centers (Figure 6b). The intensity ratio of YGM1 was 4 th times more than YGM2 suggesting that initially YGM1 was a prominent species but with time YGM2 was a prominent species.…”
Section: Epr Studymentioning
confidence: 89%
“…Electronically one centre (-NH) is hard (sp 3 ) and the other (CvN-) is soft (sp 2 ), which were tethered by a maleonitrile moiety. In order to create a strong Lewis acidity and a highly electron-withdrawing action at the metal centre at the donor site, the malenonitrile 82,83 moiety was tethered into the backbone of these ligands.…”
Section: Synthesis Of Ligands and Co-complexesmentioning
confidence: 99%
“…In this line of chemistry, our group is continuously working to contribute new and efficient catalytic systems for CO 2 fixation. We have recently reported 82,83,99 b syntheses, characterization and catalytic activity of Zn complexes of half-reduced asymmetric half-salen-type Schiff base ligands. We have shown that Zn-complexes are excellent catalysts 99 b for CO 2 fixation under mild and solvent-free conditions at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of nitrogen atoms of the diimine moiety in salen ligands by sulfur atoms recently found successful applications in the cleavage of carbon‐sulfur bond chemistry, a process useful in the desulfurization of petroleum, and the aerobic oxidative cleavage of ß‐keto‐sulfides [42] …”
Section: Introductionmentioning
confidence: 99%